“The Japanese Village” and the Metropolitan Construction of Modernity - McLaughlin, Joseph (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2007)
AbstractThis article details the history of “The Japanese Village” exhibition in late-Victorian Knightsbridge. This exhibition, which opened two months before the premier of Gilbert and Sullivan’s The Mikado in March 1885, provides an opportunity to deepen our understanding of the variety of ways Japan was represented to and by Victorian audiences. In addition to describing the event, the essay studies newspaper accounts of the exhibition's destruction by fire and subsequent rebuilding, a narrative that promotes a distinction between the picturesque ephemerality of a traditional village and the metropolitan settings in which it was staged and contained.